IMPROVING THE SPEAKING SKILL OF THE TENTH GRADE STUDENTS THROUGH ONLINE CUE CARD - Mulyana, Agus; Kurniawan, Andri; Sutiawati, Sutiawati (JIPIS, 2021)
The aim of this research was to know whether there is a significant effect of using cue card on studentsâ€™ speaking skill after applying cue card of students at the tenth grade of SMAN 12 Kabupaten Tangerang. This research is quantitative method, 80 students as the sample which taken nonrandom by using quasi experimental research non-equivalent control group design. Studentsâ€™ test were used by the researcher to collect the data. The hypotheses data was tested using formula of t- test, it was known that between experimental and control class in speaking skill got âˆ’ð‘¡ð‘ð‘œð‘¢ð‘›ð‘¡ < âˆ’ð‘¡ð‘¡ð‘Žð‘ð‘™ð‘’ (-6,509 > - 2,002) with sig = 0, 000 < 0,05, so it can be concluded that Ho is rejected and Ha is accepted it means there is significant difference used cue card on the studentsâ€™ speaking skill at the tenth grade of SMAN 12 Kabupaten Tangerang, because the condition of students in experimental class are active and had many opinions during the learning. Besides that they more easily to increase studentsâ€™ speaking skill by using cue card than control class only used conventional method. Keywords: Cue Card, Learning Media, Online Card, Speaking Skill